(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To assess the knowledge of respiratory infection prevention among medical students at the Vietnam University of Traditional Medicine in 2025. Subjects and Methods: A descriptive cross-sectional study was conducted on 908 medical students from the 3rd to 6th academic years between May and October 2025 using a structured questionnaire. Data were collected and analyzed using Excel and SPSS version 22.0. Statistical significance was set at p<0.05. Results: Among 908 students, the mean knowledge score on respiratory infection prevention increased progressively across academic years: Medical students, Year 3 (MS3) 8.95 ± 1.37, MS4 9.03 ± 1.10, MS5 9.45 ± 1.17, and MS6 9.98 ± 1.19. There was a difference in the mean knowledge scores between General Medicine students (9.44 ± 1.32) and Traditional Medicine students (9.16 ± 1.22); however, this difference was not statistically significant (p > 0.05). Conclusion: Medical students demonstrated fairly good to good levels of knowledge regarding respiratory infection prevention, which improved progressively with academic year.